Implikasi Budaya Organisasi dan Kepemimpinan Kepala Sekolah terhadap Kinerja Gurudan Kompetensi Lulusan - Syahril Syahril (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2015)
The purpose of this study was to obtain empirical evidence and conclusions regarding the influence of organizational culture, leadership of the principal, teacher competence, teacher performance, and competency. The method used explanatory methods, data analysis methods were used to test the hypothesis was path analysis. independent variables of the study are: organizational culture (X1), leadership (X2), and competence (X3), teacher performance (Y) as the intermediate variables and the dependent variable is the competence of graduates (Z). The results of this study show that: (1) organizational culture directly affects the performance of teachers, (2) the principal's leadership directly affects the performance of teachers, (3) the competence of teachers directly influence the performance of teachers, (4) organizational culture, leadership of the principal, and teacher competence simultaneously significant effect on teacher performance, (5) the performance of teachers have a significant effect on graduates' competence.